Weight Loss and Concomitant Adipose Autophagy in Methionine‐Restricted Obese Mice is Not Dependent on Adiponectin or FGF21. Issue 6 (29th April 2020) - Cooke, Diana; Mattocks, Dwight; Nichenametla, Sailendra N.; Anunciado‐Koza, Rea P.; Koza, Robert A.; Ables, Gene P.
Abstract : Objective: Identifying novel approaches to combat obesity is important to improve health span. It was hypothesized that methionine restriction (MR) will induce weight loss in obese mice by reducing adipose tissue mass caused by increased energy expenditure and reprogramming of adipose tissue homeostasis. The roles of adiponectin (ADIPOQ) and fibroblast growth factor 21 (FGF21) during weight loss in MR mice were also tested. Methods: Diet‐induced obese (DIO) male C57BL/6J (wild type), Adipoq ‐deficient ( Adipoq knockout [KO]), Fgf21 ‐KO, and Adipoq ‐ Fgf21 double‐KO mice were used. Following a switch to high‐fat control (DIO‐CF, 60% fat/0.86% methionine) or MR (DIO‐MR, 60% fat/0.12% methionine) diet, physiological parameters were measured, and inguinal and perigonadal adipose tissues were examined. Results: Obese mice subjected to MR showed loss of body weight and adiposity, increased energy expenditure, and improved glucose tolerance that were independent of the actions of ADIPOQ and FGF21. MR induced reduction of circulating lipids, glucose, insulin, leptin, and insulin like growth factor 1 and increased β‐hydroxybutyrate, ADIPOQ, and FGF21 concentrations. In fat, MR upregulated protein levels of adipose triglyceride lipase, apoptosis‐inducing factor, lysosomal‐associated membrane proteins 1 and 2, autophagy‐related protein 5, beclin‐1, and light chain 3B I and II. Conclusions: MR reduction of adipose tissue mass in obese mice is associated with elevated lipolysis, apoptosis, and autophagy and occurs independently of the actions of ADIPOQ and FGF21.